Fuels from Waste as Renewable Energy in Distributed Generation on the Example of the ORC System - Monika Czop; Nikolina Poranek; Adrian Czajkowski; Łukasz Wagstyl (Recycling, 2019)
The article compares the energetic qualities of fuels from waste with hard coal. A cogeneration system has been modeled based on the organic Rankine cycle (ORC) powered by the investigated fuels in order to identify possibilities as well as problems in use of fuels from waste in an exemplary cogeneration unit in distributed generation. The emission of thermal transition of the investigated fuels has been calculated on the basis of their energetic use in order to determine the aggregate impact on the environment, people’s health and the ecosystem. In order to conduct the research, Ebsilon Professional and SIMAPro software were used. The article demonstrated the energetic and ecological validity of the use of fuels form waste in small-scale combined heat and power (CHP). The energetic potential and influence on the environment, people’s health and the ecosystem depends on the quality of fuel, but the strict regulations for generating fuels from waste and the flexibility in forming them, allow for a product which is more beneficial economically and ecologically than hard coal.